The relationship between husband's support and exclusive breastfeeding at PMB Mira Haryanti Bangsalan Teras Boyolali - Ernawati, Ernawati; Widyastuti, Deny Eka; Umarianti, Tresia; Rohmatika, Dheny (Universitas 'Aisyiyah Yogyakarta, 2025)
Breastfeeding as the beginning of the importance of a responsive relationship between the baby and the mother, and can have a big influence in reducing the negative psychological impact of the mother and the baby, because breast milk strengthens the process of forming a psychological bond between mother and child. This study aims to determine the relationship between husband's assistance and the provision of Exclusive Breastfeeding in Breastfeeding Mothers at PMB Mira Haryanti Bangsalan Teras Boyolali. With a cross-sectional plan design. The research sample was all breastfeeding mothers at PMB Mira Haryanti as many as 30. The sampling method used in this study used total sampling. Husband's assistance in Breastfeeding Mothers at PMB Mira Haryanti Bangsalan Teras Boyolali showed that the most was good as many as 15 people (50%). Boyolali showed that the most was good as many as 15 people (50%). The provision of Exclusive Breastfeeding in Breastfeeding Mothers at PMB is the provision of Exclusive Breastfeeding as many as 21 people (70%). The Spearman Rank test showed a p value of 0.019 which means there is a relationship between Husband's Assistance and the Provision of Exclusive Breastfeeding in Breastfeeding Mothers at PMB Mira Haryanti Bangsalan Teras Boyolali. The correlation coefficient showed an r value of 0.920, indicating a strong relationship between husband's support and exclusive breastfeeding.